MCGLUE'S DEFENSE MECHANISM ACTIVATED BY TRAUMATIC EXPERIENCES: A FREUDIAN PSYCHOANALYSIS STUDY - Izzah, Aulia; Pandin, Moses Glorino Rumambo (Universitas Airlangga, 2024)
The most important thing for parents to achieve is a safe environment for their children to grow up in. Children need to be guided properly to lead a good life in the future. Psychoanalysis, a theory by Sigmund Freud, generally discusses a person's experiences in their early stage of life. This article employs psychoanalysis as the grand theory, focuses on the relationship between childhood trauma and its impact on adulthood, and implements a qualitative descriptive method to analyze the main character of Ottessa Moshfegh's novel, McGlue. The story follows McGlue, a man who suffered childhood trauma after discovering he was unfairly treated by his mother and was continuously rejected by society. It aims to analyze the causes of his trauma and how it affected the defense mechanisms that he did in his adulthood in facing reality. The defenses he did were mostly performed when his best friend, Johnson, died. When confronted with Johnson's death, he used four defense mechanisms: selective memory, regression, projection, and denial. McGlue turned into an individual who chose violence to protect himself from hurting. This study finds that his traumatic experiences made him against the world, judging by how he consumed alcohol since he was young and continuously doing illegal and irresponsible things.